A Study on Enhancement of Solubility and Dissolution Properties of Voriconazole by Solid Dispersion Technique: Research Article (Journal of Pharma Insights and Research, 2024)
Voriconazole is a triazole antifungal drug used to treat fungal infections. It works by inhibiting fungal growth. However, voriconazole has low aqueous solubility of only 0.5 mg/mL at room temperature, making it a Class II drug according to the Biopharmaceutics Classification System (BCS). This limited solubility poses challenges for developing effective oral formulations. In this study, solid dispersions of voriconazole were prepared using different methods and carriers in an attempt to improve its solubility and dissolution rate. The physical mixture, solvent evaporation, and kneading methods were used to prepare solid dispersions with polyethylene glycol 6000 (PEG 6000) or hydroxypropyl methylcellulose (HPMC) at 1:1 or 1:3 drug to carrier ratios. The formulations were characterized based on drug content, saturation solubility, Fourier transform infrared spectroscopy (FTIR), and in vitro dissolution testing. FTIR analysis indicated minor or no molecular interaction between voriconazole and the polymers, suggesting compatibility. In vitro dissolution studies showed the solid dispersion with PEG 6000 at a 1:3 ratio achieved the highest release of 97.26% of voriconazole after 30 minutes. This represents over a three-fold increase in dissolution rate compared to voriconazole alone, demonstrating the ability of these systems to enhance voriconazole's solubility and dissolution properties